Seropositivity Among Children of COVID-19 Rt-Pcr Confirmed Health Care Workers (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Coronavirus Disease 2019 (COVID-19) affects children mildly most of the cases. The study was done among the children of COVID-19 confirmed healthcare workers to see antibody response against COVID-19.Materials and methods: This cross-sectional study was conducted by the Children of COVID-19 confirmed Health Care Workers (HCWs) of Chittagong Medical College (CMC). After enrolling the HCWs, who were RTPCR  positive within the last 14 days to 6 months, blood  samples of their children were collected and tested for  COVID-19 antibody. To determine the association of different characteristics, Fisher’s exact and Mann Whitney by U test were done.Results: Total 100 Children were tested for two variants of SARS-CoV-2 Antibody, UK and African variant. SARS-CoV-2 antibodies were detected in 41% of children for both variants. The Mean Antibody titer against UK and African variants was found 83.00±11.39% and 72.30±20.68% respectively. Symptomatic children showed significantly (p-0.00) higher SARS-CoV-2 seropositivity and asymptomatic children were also capable of developing response against SARS-CoV-2.Conclusion: Antibody titers were significantly higher in symptomatic children, approximately half of children with positive antibody tests for SARS-CoV-2 reported no symptoms.JCMCTA 2025 ; 36 (2) : 118-124